Glucocorticoid-Treated Mice Are an Inappropriate Positive Control for Long-Term Preclinical Studies in the mdx Mouse - Sali, Arpana; Guerron, Alfredo D.; Gordish-Dressman, Heather; Spurney, Christopher F.; Iantorno, Micaela; Hoffman, Eric P.; Nagaraju, Kanneboyina (PLOS ONE, 2012)
Background Dmdmdx (mdx) mice are used as a genetic and biochemical model of dystrophin deficiency. The long-term consequences of glucocorticoid (GC) treatment on dystrophin-deficient skeletal and heart muscle are not yet known. Here we used systematic phenotyping to assess the long-term consequences of GC treatment in mdx mice. Our investigation addressed not only the effects of GC on the disease phenotype but also the question of whether GCs can be used as a positive control for preclinical drug evaluations. Methods and Findings We performed nine pre-clinical efficacy trials (treated N = 129, untreated N = 106) of different durations in 9-to-50-week-old dystrophic mdx mice over a 3-year time period using standardized methods. In all these trials, we used either 1 mg/kg body weight of prednisone or 5 mg/kg body weight of prednisolone as positive controls to compare the efficacy of various test drugs. Data from untreated controls and GC-treated mice in the various trials have been pooled and analyzed to assess the effects of GCs on dystrophin-deficient skeletal and cardiac muscles of mdx mice. Our results indicate that continuous GC treatment results in early (e.g., at 50 days) improvements in normalized parameters such as grip strength, motor coordination and maximal in vitro force contractions on isolated EDL muscle, but these initial benefits are followed by a progressive loss of muscle strength after 100 days. We also found a significant increase in heart fibrosis that is reflected in a significant deterioration in cardiac systolic function after 100 days of treatment. Conclusion Continuous administration of prednisone to mdx mice initially improves skeletal muscle strength, but further therapy result in deterioration of muscle strength and cardiac function associated with enhanced cardiac fibrosis. These results suggest that GCs may not serve as an appropriate positive control for long-term mdx mouse preclinical trials.